The effect of ethanol extract of mangostene (Garcinia Mangostana Linn.) peel on tongue cancer cells Supris Clone-1 apoptosis, in vitro - Titiana, Maria Aurora; Oewen, Roosje Rosita; Satari, Mieke Hemiawati (Padjadjaran Journal of Dentistry, 2011)
Apoptosis or programmed cell death serves to regulate physiological and pathological conditions. Garcinia mangostana Linn. is one of the medical herbs that is widely used to suppress human tongue cancer growth by inducing apoptosis. The research aimed to analyze the effect of ethanol extract of Garcinia mangostana Linn. on tongue cancer cells apoptosis Supris Clone-1 (SP-C1). The type of the research was an experimental laboratory. Tongue cancer cells SP-C1 were treated by various ethanol extract concentrations (0, 300, 400, 500, 600, 700 pg/ml) of Garcinia mangostana Linn. to detect the apoptosis, which was done by acridine orange and ethidium bromide coloring tests. The number of tongue cancer cells SP-C1 2x104 cells/dish. Observation on cells apoptosis was observed by a fluorescent microscope with 40 x magnification. The data were analyzed using one-way ANOVA and was followed by Post Hoc test (Tukey-test) with 95% significance level. The result showed that tongue cancer cells SP-C1 apoptosis treated by various ethanol extracts of Garcinia mangostana Linn. increase significantly. The highest effect of apoptosis was detected at the 700 pg/ml concentration that has an effect on the percentage of tongue cancer cells apoptosis by 65%.